Adverse neonatal effects of maternal labetalol treatment. Issue 2 (1st September 1998) - Crooks, B N A; Deshpande, S A; Hall, C; Platt, M P Ward; Milligan, D W A
Abstract : Two infants with features of severe β adrenergic blockade, pericardial effusions, and myocardial hypertrophy were born to mothers receiving long term treatment with oral labetalol for hypertension in pregnancy. Labetalol was implicated in the aetiology of these problems. Pericardial effusion and myocardial hypertrophy have not been associated with labetalol toxicity in neonates.